Effects of performance appraisal purpose and rater expertise on rating error - Weyhrauch, William S. (Kansas State University, 2010)
Performance appraisals are an important component to any organization’s performance management system. They require supervisors to observe and retain information regarding employee performance. This study sought to investigate the effects of appraisal purpose in this process. This extension and replication of Williams, DeNisi, Meglino, and Cafferty’s (1986) lab study of appraisal purpose investigated whether designating an employee for a positive outcome results in lenient performance ratings and vice-versa for a negative designation. This outcome would indicate assimilation, whereby the designation acts as an anchor creating bias in the direction of the anchor. However, the negative and positive designations may both result in leniency, indicating a universal tendency toward leniency when memory for performance is limited. Furthermore, I investigated whether making a deservedness rating for each employee would result in less lenient or severe ratings, relative to the designation conditions. Finally, I investigated whether self-reported rater expertise would moderate the assimilation effect. A total of 108 undergraduate students from a large Midwestern university viewed confederates performing cardio-pulmonary resuscitation (CPR) on a dummy and were instructed to observe performance in order to make a designation (positive or negative) or deservedness rating, or were given no instructions (control). They made an initial decision and were then asked to return two days later and rate each confederate’s performance again. Consistent with previous findings, raters making positive designations tended to give lenient ratings, relative to other conditions. Furthermore, as expected, those making negative designations gave relatively severe ratings. Finally, the results also partially supported my expectation that rater expertise in the performance domain moderates the biasing effects of appraisal purpose. Implications for practice and recommendations for future research are discussed.
Keywords: Performance appraisal; Assimilation; Rater expertise; Leniency; Severity; Rating error; Psychology, Industrial (0624)